Silicon isotope fractionation during microbial reduction of Fe(III)–Si gels under Archean seawater conditions and implications for iron formation genesis. (1st October 2016) - Reddy, Thiruchelvi R.; Zheng, Xin-Yuan; Roden, Eric E.; Beard, Brian L.; Johnson, Clark M.
Abstract: Microbial dissimilatory iron reduction (DIR) is a deeply rooted metabolism in the Bacteria and Archaea. In the Archean and Proterozoic, the most likely electron acceptor for DIR in marine environments was Fe(III)–Si gels. It has been recently suggested that the Fe and Si cycles were coupled through sorption of aqueous Si to iron oxides/hydroxides, and through release of Si during DIR. Evidence for the close association of the Fe and Si cycles comes from banded iron formations (BIFs), which consist of alternating bands of Fe-bearing minerals and quartz (chert). Although there has been extensive study of the stable Fe isotope fractionations produced by DIR of Fe(III)–Si gels, as well as studies of stable Fe isotope fractionations in analogous abiologic systems, no studies to date have investigated stable Si isotope fractionations produced by DIR. In this study, the stable Si isotope fractionations produced by microbial reduction of Fe(III)–Si gels were investigated in simulated artificial Archean seawater (AAS), using the marine iron-reducing bacterium Desulfuromonas acetoxidans . Microbial reduction produced very large 30 Si/ 28 Si isotope fractionations between the solid and aqueous phase at ∼23 °C, where Δ 30 Sisolid–aqueous isotope fractionations of −3.35 ± 0.16‰ and −3.46 ± 0.09‰ were produced in two replicate experiments at 32% Fe(III) reduction (solid-phase Fe(II)/FeTotal  = 0.32). This isotopic fractionation was substantially greater than that observed in two abiologic controls that had solid-phase Fe(II)/FeTotal  = 0.02–0.03, which produced Δ 30 Sisolid–aqueous isotope fractionations of −2.83 ± 0.24‰ and −2.65 ± 0.28‰. In a companion study, the equilibrium Δ 30 Sisolid–aqueous isotope fractionation was determined to be −2.3‰ for solid-phase Fe(II)/FeTotal  = 0. Collectively, these results highlight the importance of Fe(II) in Fe–Si gels in producing large changes in Si isotope fractionations. These results suggest that DIR should produce highly negative δ 30 Si values in quartz that is the product of diagenetic reactions associated with Fe–Si gels. Such Si isotope compositions would be expected to be associated with Fe-bearing minerals that contain Fe(II), indicative of reduction, such as magnetite. Support for this model comes from recent in situ Si isotope studies of oxide-facies BIFs, where quartz in magnetite-rich samples have significantly more negative δ 30 Si values than quartz in hematite-rich samples.